Struktur Pertunjukan Tari Andun dalam Upacara Perkawinan di Desa Tumbuan Kecamatan Lubuk Sandi Kabupaten Seluma Provinsi Bengkulu - Dyantika Citra Winanda; Desfiarni Desfiarni (SENDRATASIK UNP, 2023)
The aim of this research is to reveal and describe the structure of the Andun Dance  in a wedding ceremony in Tumbuan Village, Lubuk Sandi District, Seluma Regency, Bengkulu Province. This type of research is a qualitative research with descriptive method. The research instrument was the researcher himself and assisted by supporting instruments such as stationery and cameras. The data in this study uses primary data and secondary data. Data collection techniques were carried out by means of literature study, observation, interviews and documentation. The steps to analyze the data are data collection, data presentation and conclusion. The results of the study show that the structure of the Andun Dance  performance in the wedding ceremony consists of 3 parts. 1) Opening; i.e. performing bedik (Sarafal Anam). Bedikir at the wedding ceremony has the aim of conveying praise to Allah SWT, praying for the bride and groom to become a sakinah, mawaddah and warohmah family, and entertaining the family and guests with Islamic nuances. 2) Core Section; namely performing the Andun and Berejung dances. The purpose of the Andun Dance  in a wedding ceremony is to introduce and socialize between the families of the bride and groom. Andun Dance  has 3 types of movements, namely Eagle Movement, Lelayang Movement, and Saluang Ngambat Ulak Movement. Berejung in a wedding party aims to express the dancers' hearts to the bride and groom in the form of congratulations and messages in satirical language through poetry. 3) Cover; namely showing Mencak. The purpose of Mencak in a wedding ceremony is toughness, a man's dexterity in protecting his family.